G172 Neonatal Seizures: The Utility of Magnetic Resonance Imaging in Diagnosis and Prediction of Neurodisability. (4th June 2013) - Billetop, A; Osmond, E; Jary, S; Tsakmakis, MV; Gowda, K; Likeman, M; Thoresen, M; Luyt, K
Abstract : Aim: To determine the etiological association, neurodevelopmental sequelae and role of Magnetic Resonance Imaging (MRI) in term newborn infants with seizures. Methods: Cohort study of infants >37 weeks gestation delivered in a single level 3 centre in the UK from 1/12/2004 to 31/10/2009 (59 months), prospectively identified by a perinatal morbidity surveillance system and followed longitudinally for 18–24 months. Results: 77 infants were identified with seizures during the study period (3.0/1000 live births). 9 infants died (12%). 73/77 (95%) had an aEEG recording and 70/77 (91%) had an MRI scan. In 95% of cases an underlying cause of seizures was elucidated. The most common diagnosis was HIE (65%) with neonatal stroke as the second most common diagnosis (12%). Overall, 28/77 (36%) of the cohort had a neurodevelopmental impairment (NDI), ranging from mild to severe. 37/50 infants with HIE (74%) received therapeutic hypothermia and 9 (24%) had NDI. Of the remaining 13 managed with normothermia, 4 had NDI (31%). NDI was prevalent in those with a diagnosis other than HIE (15/27; 56%), in particular stroke, hypoglycaemia and cerebral dysgenesis. 15/77 (19%) had recurrence of seizure in the first 2 years of life. The highest risk of seizure recurrence was in cerebral dysgenesis, hypoglycaemia and stroke. Infants with HIE had a very low risk of seizure recurrence (1/50; 2%). 45/70 (64%) had abnormal MRI findings. The negative predictive value of a normal MRI in survivors of developing any disability was 0.93. Conclusion: This is the first report of a cohort of term infants with seizures fully investigated by MRI and aEEG. HIE was the most common cause of seizures in this population. Neonatal stroke was the most likely diagnosis for term infants presenting with seizures on day two of life. The universal use of MRI allows a cause to be identified in 95% of term infants with seizures. A normal MRI scan was highly predictive of a normal neurodevelopmental outcome. There was significant risk of NDI and seizure recurrence, particularly in those with a diagnosis other than HIE, supporting formal neurological surveillance.